Bacillus Calmette-Guérin immunotherapy—increasing dose as a means of improving therapy? - Mahendran, Ratha (Translational Cancer Research, 2017)
Bladder cancer is not life threatening but it is characterized by frequent recurrences which may progress to muscle invasive disease. The standard therapy for intermediate and high grade non muscle invasive bladder cancer is tumor removal followed by Mycobacterium bovis, Bacillus Calmette-Guérin (BCG) immunotherapy. This consists of weekly intravesical instillations of BCG that are divided into induction and maintenance phases. BCG immunotherapy stimulates the immune system and this leads to tumor removal. While BCG immunotherapy is regarded as the most successful immunotherapy, it is associated with side-effects that can in some cases be so severe that patients cannot complete this therapy. Those who fail to complete therapy are more likely to have a recurrence. Some 30–50% of patients will have a recurrence despite therapy. Thus most clinical and laboratory analyses are aimed at improving the response to BCG immunotherapy and trying to identify those will respond to therapy from non-responders. These are not trivial problems as clinical studies on BCG immunotherapy are not all similar. These studies are conducted in different countries and use different BCG strains, doses and schedules of therapy such as frequency of induction and maintenance instillations. Patient genetic polymorphisms and tumor characteristics are also known to impact response to therapy. These differences do make improving BCG therapy challenging. A recent study has proposed a novel strategy of dose increase to improve BCG induced cytotoxicity. The study is discussed in the context of our current knowledge of the response to BCG immunotherapy.